CONSUMPTION PARAMETERS OF ELECTRODES WITH ASH AND MARABOU CHARCOAL IN A PERIPHERAL COATING - Cruz Díaz, Maykel; Cruz Crespo, Amado; Acevedo Pérez, Manuel; Duffus Scott, Alejandro; Najarro Quintero, Rodolfo; Díaz Cedré, Eduardo M. (Centro Azúcar Journal, 2025)
Introduction: Hardfacing consumables to combat abrasion are expensive, leading to shortages in agricultural areas. However, welding electrodes are inexpensive, so converting them to hardfacing by applying peripheral coating with residuals represents an opportunity. Objective: To establish the effect of marabou charcoal content in the peripheral coating of AWS E7018 electrode converted for overlay and of the welding current on the consumption parameters. Materials and Methods: An experimental design study was conducted to study the behavior of consumption parameters (consumption, deposition, and efficiency) of an AWS E7018 electrode converted to hardfacing by applying a peripheral coating with ash and marabou charcoal. The deposit hardness of the best-performing electrode was determined and compared with that of the electrode without a peripheral coating and with that of a harrow disc. Results and Discussion: The relationships between consumption parameters and the marabou carbon content in the electrode and the welding current as independent variables are established. Behavioral trends in the responses are explained phenomenologically. Conclusions: The best condition of marabou carbon content in the electrode coating (50%) and welding current (115 A) is defined to ensure the best performance of consumption parameters and to promote an adequate deposit for coating working elements of farming implements with AWS E7018 electrode converted to hardfacing consumable.